(untitled) (UNIZIK Journal of STM Education, 2025)
Amidst students’ perception of Mathematics as abstract and difficult, augmented reality (AR) offers a dynamic and interactive instructional approach to enhance learning engagement. Therefore, this study examined the effect of Augmented Reality (AR) tools on student engagement in Mathematics in the Aba Education Zone, Abia State, Nigeria. Two research questions and two hypotheses guided this study. The hypotheses were tested at 0.05 level of significance. The study adopted a one-group pretest-posttest quasi-experimental design. A sample of 60 Senior Secondary School Two (SS2) students identified as low-achievers was drawn from a population of 9,274 SS2 students using a multistage sampling technique. The Mathematics Engagement Scale (MES) with a reliability coefficient of 0.85, was used for data collection. Mean, standard deviation, and paired t-tests were used for data analysis. Results showed that AR significantly enhanced student engagement. The study recommended integrating AR into Mathematics teaching to support low-achieving learners and promote inclusive, technology-enhanced learning.